Renal perfusion improvement in the perioperative period after unilateral endovascular revascularization in patients with atherosclerotic renal artery stenosis - Xu, Leyin; Shao, Jiang; Li, Kang; Wang, Chaonan; Lai, Zhichao; Ma, Jiangyu; Yu, Xiaoxi; Du, Fenghe; Chen, Junye; Liu, Xiaolong; Yuan, Jinghui; Liu, Bao; et al. (Frontiers in Cardiovascular Medicine, 2023)
Background The clinical benefits of endovascular treatment in renal artery stenosis (RAS) remain controversial. This study used an intraoperative renal perfusion imaging technique, called flat-panel detector parenchymal blood volume imaging (FD-PBV), to observe the change in renal perfusion after endovascular treatment in RAS. Materials and methods In a prospective, single-center study, we assigned 30 patients with atherosclerotic RAS who underwent endovascular treatment between March 2016 and March 2021. The preoperative and postoperative results of renal perfusion, blood pressure, and renal function, were compared. Results Both median kidney volume (p < 0.001) and median preoperative mean density of contrast medium (MDCM) (p = 0.028) increased significantly after endovascular treatment. The ratio of postoperative and preoperative MDCM differed greatly among the patients. For patients with preoperative MDCM <304.0 HU (Subgroup A, 15 cases), MDCM significantly increased after treatment (p = 0.001) and 12 (80.0%) patients had more than 10% increase in renal perfusion. For patients who had relatively high preoperative renal perfusion (MDCM ≥304.0 HU, Subgroup B, 15 cases), preoperative and postoperative MDCM were similar (p = 0.776). On the other hand, the serum creatinine levels significantly decreased in Subgroup A (p = 0.033) and fewer antihypertensive drugs were used after endovascular revascularization (p = 0.041). The preoperative and postoperative creatinine levels and number of antihypertensive drugs were similar in Subgroup B. Conclusions During the perioperative period, RAS patients with relatively low preoperative renal perfusion levels had greater improvement in renal perfusion, renal function, and blood pressure control after endovascular treatment. The improvement of renal function needs to be confirmed by long-term follow-up.